Three-dimensional kinematic analysis of horses with induced tarsal synovitis - Khumsap S. (2014)
Reasons for performing study: Techniques for 3D analysis have recently been developed. This study applied 3D kinematic analysis to describe the effects of lameness in the distal intertarsal (DIT) and tarsometatarsal (TMT) joints; complex joints such as this may show measurable amounts of movement outside the sagittal plane that may change in response to pathological conditions. Hypothesis: Three-dimensional motions of the tarsal joint change after the induction of synovitis at the DIT and TMT joints. Methods: Twelve retroreflective markers, attached on the skin over the right limb, were used to develop 3D coordinate systems for tibial and metatarsal segments. Data were collected at trot from 4 horses on 2 occasions, before (sound condition) and after (lame condition) induction of synovitis of the DIT and TMT joints. Ranges of 3D motions of the metatarsal segment relative to the tibial segment were compared between sound and lame conditions using t tests. Results: There were significant decreases (P<0.05) in tarsal joint flexion and cranial translation of the metatarsus relative to the tibia during stance, and in proximal translation of the metatarsus during swing. Conclusions and potential relevance: In the lame condition, reduced cranial translation at the DIT and TMT joints may lead to a reduction in the motion of the articular cartilage surfaces relative to each other, which may have adverse effects on cartilage nutrition and function. Further studies of tarsal 3D kinematics in horses with bone spavin could allow quantification of the biomechanical effects of the special shoes used for conservative treatment.